(untitled) (International Journal of Food and Nutritional Sciences, 2022)
-The present study was conducted to evaluate the groundwater quality of selected locations in Minority (Special Reference to Muslim villages) areas of Kishangarh block of Alwar District for drinking and irrigation purposes. A total of 15 groundwater samples were collected in Pre Mansoon Session for a period from March 2020 to June 2020.The groundwater samples were analyzed for physicochemical properties, major cations (Ca2+ , Mg2+ , K+ ) and anions (Cl− , NO3 −, F − , SO4 2− ) in the laboratory using the standard procedures of the American Public Health Association(APHA).